Menulis Skenario Secara Fair Use dengan Menggunakan AI - Aan Setiadarma; Priyono Sadjijo; Ahmad Zaki Abdullah (Universitas Muhammadiyah Manado, 2024)
The training Writing Screenplays Using Fair Use with AI was conducted to enhance participants' understanding of the fair use concept and the application of artificial intelligence (AI) technology in screenplay writing. In the digital age, AI offers great potential in the creative industry, but its use must be accompanied by a proper understanding of ethics and law. This training aimed to introduce the principles of fair use and how to use AI software to improve creativity and efficiency in writing screenplays. The methods used included lectures, practical exercises, and evaluation of participants' work. A total of 16 participants were involved in the training, which covered topics on fair use, AI application in screenplay writing, and the challenges and obstacles encountered. The results showed an increase in participants' understanding of fair use, followed by their ability to use AI to produce more efficient and creative screenplays. However, some technical and conceptual challenges were still found, such as difficulties in using AI software and limited understanding of fair use limitations. In conclusion, this training successfully raised participants' awareness of ethics and legality in the use of technology in the creative industry, with recommendations for improving materials and technical support in the future